2019
DOI: 10.2147/ijn.s199219
|View full text |Cite
|
Sign up to set email alerts
|

<p>Multilayered composite coatings of titanium dioxide nanotubes decorated with zinc oxide and hydroxyapatite nanoparticles: controlled release of Zn and antimicrobial properties against <em>Staphylococcus aureus</em></p>

Abstract: Purpose: This study aimed to decorate the surface of TiO 2 nanotubes (TiO 2 NTs) grown on medical grade Ti-6Al-4V alloy with an antimicrobial layer of nano zinc oxide particles (nZnO) and then determine if the antimicrobial properties were maintained with a final layer of nano-hydroxyapatite (HA) on the composite. Methods: The additions of nZnO were attempted at three different annealing temperatures: 350, 450 and 550 °C. Of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Combining materials can have a synergistic effect as it was demonstrated that TiO 2 /ZnO nanoparticles supported in 4A zeolite could lead to resilient activity as antimicrobial agents [ 72 ]. In fact, multilayered composite coatings of TiO 2 nanotubes combined with ZnO and hydroxyapatite nanoparticles were applied for controlled Zn release for antimicrobial activity against Staphylococcus aureus [ 73 ]. Biological compatibility of TiO 2 coatings by changing the surface chemical composition and nanotopography has supported its use in biomedical TiO 2 applications [ 74 ].…”
Section: Biomedical Materialsmentioning
confidence: 99%
“…Combining materials can have a synergistic effect as it was demonstrated that TiO 2 /ZnO nanoparticles supported in 4A zeolite could lead to resilient activity as antimicrobial agents [ 72 ]. In fact, multilayered composite coatings of TiO 2 nanotubes combined with ZnO and hydroxyapatite nanoparticles were applied for controlled Zn release for antimicrobial activity against Staphylococcus aureus [ 73 ]. Biological compatibility of TiO 2 coatings by changing the surface chemical composition and nanotopography has supported its use in biomedical TiO 2 applications [ 74 ].…”
Section: Biomedical Materialsmentioning
confidence: 99%
“…The hydrothermal method has been widely used in the preparation of ZnO with nanorod structures. Changing the factors, such as reaction temperature, vessel pressure, and reaction time, may affect the growth of ZnO nanocrystals on the substrate surface [ 74 , 75 ]. Seed layers can be prepared on the surface of Ti substrates and then hydrothermally treated to aid their growth [ 76 , 77 ], or nano-ZnO can be prepared directly on the substrate surface in a sealed pressure vessel [ 74 ].…”
Section: Fabrication Of Nano-zno Modified Ti Materials and Their Biosafe Propertiesmentioning
confidence: 99%
“…HA has almost the same chemical composition as natural bone and teeth, and the size and rigidity of nano-sized HA (nHA) are highly similar to those of HA crystals in natural bone; thus HA has good biocompatibility and osteoinductive activity, and is often used as a coating material [ 121 , 122 ]. Therefore, some scholars obtained better biocompatibility and osteoinductivity while achieving a good antibacterial effect when nano-ZnO was doped with nHA [ 70 , 75 ]. In the latest research, polypyrrole (PPy) was used as a dual regulator of nHA and nano-ZnO through coordinating and doping of ions, which reduced the release rate of Ca 2+ and Zn 2+ , not only ensuring a good antibacterial effect but also improving the physiological stability of the composite coating [ 61 ] (Fig.…”
Section: Antimicrobial Activity Of Nano-zno Modified Ti Implantsmentioning
confidence: 99%
“…[71] The liberation of oxygen species on the surface of ZnO can significantly damage microorganisms. [73] Zn is effective against S. aureus, [74] Porphyromonas gingivalis and Actinomyces naeslundii, [73] Escherichia coli, [71] Streptococcus sobrinus, [16,75] and S. mutans. [76] Zinc oxide nanoparticles have photocatalytic activity and high stability.…”
Section: In Vitro Studiesmentioning
confidence: 99%